IMPLEMENTASI SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN (SIMPEG) DI MADRASAH DALAM MEWUJUDKAN TATA KELOLA PEGAWAI (STUDI MULTI KASUS DI MTS NEGERI 1 DAN MTS NEGERI 3 KOTA SURABAYA) - Kamelia Musa’ad; Kaniati Amalia; Ayu Wulandari; Muffarihul Hazin; Ima Widiyanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Personnel Management Information System (SIMPEG) at MTs Negeri 1 and MTs Negeri 3 Surabaya using a qualitative approach with a multi-case study design. Data were collected through in-depth interviews, observations, and documentation, and their validity was tested using source and technique triangulation. The findings show that the implementation of SIMPEG in both madrasahs has gone through the stages of execution and evaluation. The implementation of SIMPEG has proven to accelerate personnel services, although it still requires technical assistance and simplification of workflows to enhance user-friendliness. Meanwhile, periodic evaluations are utilized to improve procedures, enhance data quality, and serve as a basis for structuring teachers’ ranks, grades, and positions. SIMPEG has a positive impact on teacher professionalism through the availability of performance data, training histories, self-development records, as well as the strengthening of orderly administrative culture and work discipline. At the same time, it reinforces data-based teacher governance, minimizes misunderstandings in personnel services, and supports leadership decision-making related to assignments and career development. Supporting factors for SIMPEG implementation include policy support from the Ministry of Religious Affairs and madrasah leaders, the availability of ICT facilities and internet networks, the presence of competent operators, and a culture of mutual assistance among teachers. In contrast, inhibiting factors include limited information technology skills among some teachers, heavy teaching workloads, technical system and network constraints that are not always accompanied by detailed technical guidelines. The implications of this study emphasize that optimizing SIMPEG requires strengthened continuous assistance, improved digital literacy, reorganization of administrative workloads, and consistent data updating so that SIMPEG truly functions as a strategic instrument in personnel governance and teacher professional development.